OFG-STM: Transactional Memory for GPUs based on Obstruction-Free STM algorithms - Perlin, Tiago; Cavalheiro, Gerson; Du Bois, André Rauber (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2024)
Transactional memory is a high-level programming abstraction for synchronizing concurrent tasks investigated in different architectures, such as multicores, distributed systems and GPUs. Software transactional memory systems (STMs), including those for GPUs, are usually implemented using a lock-based system, where the locks that protect memory locations being accessed by a transaction are acquired, either at commit time or during transaction execution, to guarantee the atomicity of the transaction’s changes to memory. Transactional memory systems can also be lock-free or obstruction-free. Still, such STM algorithms are complex to implement in languages that do not support garbage collection, as they rely on a structure called locator, which must be used to acquire ownership of transactional objects. Every time a transaction needs to access an object in write mode, a new locator is created to substitute the current locator of the object. As transactions can be aborted at any time, and concurrent transactions must read the locators of objects to access their current versions, it is difficult to know when exactly such a locator is not being used and can be freed, a common problem in designing lock-free data structures. This paper presents OFG-STM, an STM system for GPUs inspired by obstruction-free STM algorithms. OFG-STM takes advantage of the fact that GPU threads executing the same kernel execute the same code, and threads in a warp execute a kernel in lockstep, to introduce a garbage-collection phase every time a number of transactions has committed. This paper presents the design and implementation of the OFG-STM system, as well as experiments demonstrating its usability.